Science, information, and policy interface for effective coastal and ocean management - MacDonald, Bertrum H. (CRC Press, 2016)
This book provides a timely analysis of the role that information-particularly scientific information-plays in the policy-making and decision-making processes in coastal and ocean management. It includes contributions from global experts in marine environmental science, marine policy, fisheries, public policy and administration, resource management.
Keywords: Coastal zone management.; Marine ecosystem management.; Marine resources -- Management.; Nature.; Écosystèmes marins -- Gestion.; Littoral -- Aménagement.; BUSINESS & ECONOMICS -- Real Estate -- General.; Coastal zone management; Marine ecosystem management; Marine resources -- Management; Meeresressourcen; Ökosystemmanagement; Information und Dokumentation; Electronic books.